Professional Development оf Teachers For The Implementation of Quality Scienceand Mathematical Education in the Context of War in Ukraine - Vorotnykova, Iryna (Educological discourse, 2023)
The article highlights the possibilities and features of the professional development of teachers of mathematics and natural sciences in the conditions of war in Ukraine. The study is based on the analysis of the results of a survey of more than 200 teachers of the city of Kyiv regarding the provision of high-quality science and mathematics education in the conditions of war. The results of the study outline the directions of professional development of teachers of natural sciences and mathematics: the introduction of integrated education (STEM), psychological support of participants in the educational process, the use of digital and distance learning technologies, topics on life safety, inclusion, teaching methods New Ukrainian school, including the use of formative assessment, implementation of the State Standard of Basic Secondary Education. In the conditions of war, mathematics and natural sciences teachers need programs of professional development in distance, face-to-face and mixed forms of education and individual coaching. Digital technologies can help intensify postgraduate teacher education, and make it mobile, diverse, and adaptable in wartime. Educators believe that quality education can be provided under the conditions of the necessary availability of gadgets, access to the Internet, electronic educational resources, digital and distance technologies, blended learning, monitoring of educational achievements and professional development of teachers and unloading of educational programs. More than 60% of the teachers of Kyiv believe that the quality of science and mathematics education has deteriorated, and 7% point to its improvement. The analysis of interviews and surveys of teachers showed the importance of introducing individual trajectories of teachers' professional development, providing them with psychological and pedagogical support, and consultations in the postgraduate education system. The generalization of the areas of professional development of teachers should be considered in postgraduate pedagogical education for the creation and updating of educational programs for professional development.